Endocrine Measurements and Calving Performance of Swedish Red and White and Swedish Holstein Dairy Cattle with Special Respect to Stillbirth - Gustafsson H; Kindahl H; Franzén G; Kornmatitsuk B (Acta Veterinaria Scandinavica, 2003)
During 3 consecutive calving seasons, calving performance, placental characteristics and endocrine profiles of total 98 pregnancies of late pregnant Swedish Red and White (SRB) and Swedish Holstein (SLB) dairy heifers and cows, were investigated. Ninety-four singleton pregnancies and 4 sets of twins were recorded. In animals with singleton pregnancy, 8 stillbirths, 7 weak calves, 3 premature parturitions and 1 abortion were registered. In the SLB heifers, 19% of stillbirth (5/26) were observed, while 5% (2/42) were noted for the SRB heifers. One stillborn calf derived from the SRB cows and none was found from the SLB cows. In the heifers and cows delivering a normal living calf with unassisted parturition, the placentome thickness monitored by ultrasonography was constant towards the end of pregnancy. The numbers of foetal cotyledons varied individually between animals but in total, fewer cotyledons were found in the foetal membranes of the SRB animals than in the SLB animals (69 ± 19) vs. (88 ± 29) (p < 0.05). No morphological and numerical differences of the placentome thickness in animals delivering a stillborn or weak calf, compared to animals delivering a normal living calf, could be observed. In animals with unassisted parturition and without birth complications, the levels of progesterone (P4), PGF2α metabolite (PG-metabolite), cortisol, oestrone sulphate (E1SO4) and pregnancy associated glycoproteins (PAGs) were not different by breeds and parities. In animals carrying stillbirth, higher levels of E1SO4 were found in 3 SRB animals and 1 SLB heifer, whereas lower levels of E1SO4 were recorded in 3 SLB heifers during the last week of pregnancy, compared to the profiles found in animals with unassisted parturition. Additionally, the levels of PAGs remained low and constant in 1 SRB cow (delivering a stillborn calf), 1 SRB heifer (giving birth prematurely), 4 animals (carrying twins) and 1 aborting SRB cow. Our results show a very high rate of stillbirth in especially SLB heifers and deviating profiles of E1SO4 and PAGs in animals with impaired parturition were recorded.